Comparative Study of Functionalized Carbosilane Dendrimers for siRNA Delivery: Synthesis, Cytotoxicity, and Biophysical Properties - Müllerová, Monika; Tarach, Piotr; Strašák, Tomáš; Cuřínová, Petra; Petrickovic, Roman; Závodná, Táňa; Topinka, Jan; Janaszewska, Anna; Klajnert-Maculewicz, Barbara; Červenková Št'astná, Lucie (ACS omega, 2025)
Efficient and safe carriers of genetic material are crucial for advancing gene therapy. Three new series of cationic dendritic nanocarriers based on a carbosilane scaffold, differentiated by peripheral modifications: saccharide (CS-glyco), amine (CS-N), and phosphonium dendrimers (CS-P) were designed for binding, protecting, and releasing polyanionic compounds like therapeutic siRNA. Besides introducing synthetic methodology, this study brings a unique direct interstructural comparison of 16 dendritic nanovector's characteristics, addressing a gap in typical research that focuses on uniform structural types. The study evaluates the dendrimer's in vitro cytotoxicity, biophysical properties, and complexation capabilities in comparison with widely used PAMAM dendrimers. CS-glyco and PAMAMs were significantly less toxic to MCF-7 and THP-1 cell lines than were CS-N and CS-P, despite having the same peripheral charge density. Notably, CS-glyco maintained biocompatibility comparable to analogous neutral CS glycodendrimers, underscoring the exceptional capability of sugar coating to reduce toxicity. Dendriplexes formed from these nanocarriers protected siRNA from RNase degradation and facilitated its release in the presence of heparin, highlighting its potential in gene delivery applications. The study provides a background for future in-depth investigations into the introduced dendritic nanocarriers, which show significant potential for advancing drug delivery.